2020
DOI: 10.1093/nar/gkaa343
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tune control of targeted RNAi efficacy by plant artificial small RNAs

Abstract: Eukaryotic RNA interference (RNAi) results in gene silencing upon the sequence-specific degradation of target transcripts by complementary small RNAs (sRNAs). In plants, RNAi-based tools have been optimized for high efficacy and high specificity, and are extensively used in gene function studies and for crop improvement. However, efficient methods for finely adjusting the degree of induced silencing are missing. Here, we present two different strategies based on artificial sRNAs for fine-tuning targeted RNAi e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…We observed that phasiRNA accumulation is extremely variable when comparing between kits (Supplemental Figure 4, Supplemental table 2). As described before (28,29), most phasiRNAs from a single PHAS locus accumulate to diverse levels (Supplemental Figure 4, Supplemental table 2). The biogenesis of phasiRNAs by processive activity of Dicer should yield phasiRNA duplexes from a given locus in stoichiometrically equal levels; yet, of tens of thousands of reproductive phasiRNAs only a small proportion are abundant and observed in nonstoichiometric abundances within a PHAS locus (28).…”
Section: Phasirna Accumulation Is Extremely Variable At All Levelsmentioning
confidence: 70%
“…We observed that phasiRNA accumulation is extremely variable when comparing between kits (Supplemental Figure 4, Supplemental table 2). As described before (28,29), most phasiRNAs from a single PHAS locus accumulate to diverse levels (Supplemental Figure 4, Supplemental table 2). The biogenesis of phasiRNAs by processive activity of Dicer should yield phasiRNA duplexes from a given locus in stoichiometrically equal levels; yet, of tens of thousands of reproductive phasiRNAs only a small proportion are abundant and observed in nonstoichiometric abundances within a PHAS locus (28).…”
Section: Phasirna Accumulation Is Extremely Variable At All Levelsmentioning
confidence: 70%
“…Most of the contributions on antiviral strategies using SIGS have come from the lab of Carbonell et al (2019a , b) , Cisneros and Carbonell (2020) , Lopez-Dolz et al (2020) . Carbonell’s group has worked extensively on a deadly RNA virus, namely, TSWV.…”
Section: Genetic Engineering For Virus Resistance With Secondary Sirnmentioning
confidence: 99%
“…Controlling the degree of induced gene silencing to fine-tune it, keeping the promoter of the expression of silencing sRNAs invariant, is a very desirable objective but not so easy to achieve. Carbonell’s group has revealed the strategies to achieve the same by playing with the order of positioning (with respect to the cleavage point of the initiator miRNA) of the expressed syn-tasiRNAs and tweaking the sequences of the same ( Lopez-Dolz et al, 2020 ). The investigators have shown that the level and activity of Arabidopsis TAS1c-based syn-tasiRNAs gradually reduce as the syn-tasiRNA is expressed from positions more distant to the trigger miR173 cleavage site.…”
Section: Genetic Engineering For Virus Resistance With Secondary Sirnmentioning
confidence: 99%
“…On the other hand, TAS precursors possess a "natural" multiplexing capability allowing the insertion of multiple syn-tasiRNAs in a single construct (Figure 3). This feature combined with the availability of high-throughput syn-tasiRNA "B/c" vectors [7,49] allows for the efficient generation of antiviral syn-tasiRNA constructs. An interesting possibility is to combine in a single syn-tasiRNA construct a number of effective amiRNAs previously identified in large screens.…”
Section: Co-expression Of Multiple Art-srnas For Viral Rna Multi-targmentioning
confidence: 99%
“…Although very popular, these approaches lacked high specificity as the large populations of sRNAs produced from these type of precursors favor the accidental targeting of complementary cellular transcripts [6]. This limitation was overcome with the development of a series of tools based on artificial sRNAs (art-sRNAs) [7], 21-nucleotide sRNAs expressed in planta from endogenous sRNA precursors and computationally designed to silence target RNAs with high specificity [8].…”
Section: Introductionmentioning
confidence: 99%